Dauru Syabkaat al-Tawashul al-Ijtima’e fi Nasyri al-Tarbiyah al-Islamiyah wa ‘Ulumiha:: Facebook Model - Abdul Mumin Ibrahim (Aqlamuna: Journal of Educational Studies, 2023)
The research aims to identify the concept of social networking, as well as identifying the role of social networking in disseminating Islamic education and its sciences, Facebook as a model. It also aims at strategies for using social networking - Facebook - in disseminating Islamic education and its sciences. The research followed the descriptive method as the method used. The research is expected to conclude that social media networks have a great role in spreading Islamic education and its sciences, and that the networks have negatives, including pornography in images, speech, and sound, teaching intellectual extremism, sectarianism, and religious sects. The research suggests conducting further studies on the role of social media networks in disseminating Islamic education and its sciences. Holding seminars, conferences and workshops to highlight the role of social media networks in spreading Islamic education and its sciences. Raising awareness of strategies for using social networks to spread Islamic education and its sciences. Combating the negatives of using social media networks in particular and in Islamic education and sciences in general.